COVID-19 And Its Impact On Human Trafficking – Global and National Trends - Bankova, Viola (Research Papers, 2024)
The COVID-19 pandemic causes serious economic and social consequences at a global level, which affect the problem of human trafficking. The pandemic is not the cause of human trafficking, but it can intensify the factors that contribute to the exploitation of people, especially those from the most vulnerable sectors. The aim of this publication is to analyze the impact of COVID-19 on human trafficking worldwide, with a focus on Bulgaria. We will explore how COVID-19 has changed the dynamics of human trafficking, how the conditions for exploitation of the victims have changed and what measures have been taken to combat human trafficking in the period of the pandemic.